Epitope mapping of African swine fever virus p72 capsid protein using polyclonal swine sera and monoclonal antibodies - Phillips, Mallory Elizabeth (Kansas State University, 2016)
African swine fever is a hemorrhagic disease of domestic pigs caused by African swine fever virus (ASFV), a double-stranded DNA virus and the only member of the family Asfarviridae. The structure of this multilayer virion contains more than 34 proteins including the protein p72 which is the major capsid protein. A single conformational neutralizing epitope has been identified on p72, but information on the other antigenic regions (epitopes) is lacking. The objective of this study was to identify p72 epitopes using polyclonal swine sera and a panel of monoclonal antibodies with the ultimate goal being the development of a blocking ELISA assay for the detection of anti-ASFV antibodies. The segment of the p72 protein from amino acids 1 to 345 was divided into five overlapping fragments which were then commercially synthesized. These fragments were cloned into the pHUE expression vector and transformed into Escherichia coli competent cells. The recombinant proteins were expressed in vitro, purified, and used as antigens in indirect ELISAs and western blots to test monoclonal antibodies and polyclonal swine sera. The monoclonal antibodies were produced against the p72 protein based on the ASFV Georgia/07 strain. The polyclonal sera were obtained from pigs immunized with a defective alphavirus replicon particle, RP-sHA-p72, expressing a recombinant protein composed of the extracellular domain of the ASFV HA protein together with the whole p72 protein. The polyclonal sera reacted to p72 in two distinct regions: between amino acids 1 and 83 and between amino acids 250 and 280. The anti-p72 reactive monoclonal antibodies reacted with p72 in three regions: between amino acids 100 and 171, amino acids 180 and 250, and amino acids 280 and 345. Fine mapping with oligopeptides allowed for the identification of six different linear epitopes. Among the monoclonal antibodies selected for blocking assay development, two have been shown to be promising candidates for further evaluation using sera from ASFV-infected pigs.
Keywords: Epitope Mapping; Diagnostic Assay DevelopmentAfrican swine fever virus